Perancangan Ide Bisnis Produk Aromaterapi Fraise - Ade Kumala Putri; Shienny Sutanto (Universitas Ciputra Surabaya, 2018)
This research contains the business idea of aromatherapy products, which aims to see what people think about aromatherapy with modern packaging in Indonesia. The methods which are used in this research are the methods of collecting data qualitatively and quantitatively by data extraction through interviews with expert and extreme users, questionnaries to potential customers, and literature studies. This research concludes that Fraise’s Aromatherapy Balm can be an effective solution for people who need a relaxation as well as both physically and mentally tranquilities, but do not have much free time. Based on all the positive responses obtained in this research, this business idea has a considerable opportunity and the sustainability of this aromatherapy business is also quite assured.